Complications of PORT-A-CATH® in patients with sickle cell disease - Salam Alkindi; Samaa Matwani; Alghalia Al-Maawali; Buthaina Al-Maskari; Anil Pathare (Journal of Infection and Public Health, 2012)
Summary: Background: Red cell exchange/transfusion is frequently used in the management of patients with medical complications related to acute severe sickle cell disease (SCD). However, peripheral venous access is often difficult without central venous catheters (CVCs) in adult patients with moderate or severe SCD. Aims: To review our experience with the use of the PORT-A-CATH® device in sixteen patients with SCD undergoing exchange or simple transfusions. Methods: Among a cohort of 550 patients who frequently visited the inpatient service, sixteen SCD patients required the insertion of a PORT-A-CATH® device. These patients included 3 males and 13 females, aged 25–44 years [31.1 ± 2.3; mean ± SD]. A total of 24 PORT-A-CATH® devices were implanted in these 16 patients during the study period. Eleven patients had 1 device implanted, three patients had 2 devices, one patient had 3 devices, and one patient had 4 devices implanted. Results: Out of the 24 devices implanted, 17 required removal, due to either infection associated with sepsis and/or thrombosis. The organisms involved were Candida spp. (3), C. Parapsilosis (2), C. albicans (1), C. famata (1), C. lusitanice (1), Staphylococcus spp. (6), and S. aureus (3), as well as the coagulase-negative Staphylococcus (2), alpha hemolytic Streptococcus (1), Diphtheroid bacilli (2), Pseudomonas aeruginosa (2), Ps. Spp. (3), Escherichia coli (3), Klebsiella oxytoca (1), Klebsiella pneumoniae (1), Klebsiella spp. (1), Serratia liquefaciens (1), Serratia fanticola (1), Achromobacter spp. (2) Chromobacterium violaceum (1), Delftia acidovirans (1), Stenotrophomonas maltophile (1), Alcaligenes faecalis (1), and Enterobacter cloacae (1). Two episodes of documented thrombosis were observed. One case presented with right atrial thrombosis/SVC syndrome and the other case presented with left upper arm thrombosis. Two patients died with ports in situ, while five patients had ports in place at the time of this study. The median working life of the ports was 688.5 days (range: 39–3925). The rate of infective complications was 2.63 infections per 1000 catheter days, and the number of infections was significantly correlated with the number of ports [Pearson's r = 0.66; p < 0.01]. Discussion: Our results suggest that patients with SCD suffer infective complications associated with the PORT-A-CATH®, which often necessitate its removal. Although these devices are extremely useful, their optimal beneficial potential is only realized if the patients receive proper care at special centers well-versed in the maintenance of such devices by experienced staff. Keywords: PORT-A-CATH®, Sickle cell disease, Infections, Complications